2011
DOI: 10.1016/j.geotexmem.2010.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Deformation and consolidation around encased stone columns

Abstract: a b s t r a c tA new analytical solution is presented to study soft soil improvement by means of encased stone columns to reduce both settlement and consolidation time. The proposed solution aims to be a simple and useful tool for design. Only a unit cell, i.e. an end-bearing column and its surrounding soil, is modelled in axial symmetry under a rigid and uniform load. The soft soil is treated as an elastic material and the column as an elasticeplastic material using the MohreCoulomb yield criterion and a nona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(27 citation statements)
references
References 10 publications
(19 reference statements)
0
21
0
6
Order By: Relevance
“…Bu analitik yaklaşım ile yapılan parametrik çalışmalarda odometrik elastisite modülü değeri, iyileştirme faktörü ve oturma azaltma faktörü ile lineer olmayan bir değişim göstermektedir (Şekil 4). Odometrik elastisite modülü oranının oturma azalma faktörüne etkisi Castro ve Segaseta [6] yöntemine benzer sonuçlar vermektedir ancak değerler daha düşük elde edildiği için daha güvenli tarafta kalmaktadır. İki yöntem de kolon ve zeminin deformasyonu için elastisite teorisini esas almış olsa da, Balaam ve Booker [4]'in yanal deformasyonların yatay bileşenini hesaba katması daha muhafakazar sonuçlar vermektedir.…”
Section: Balaam Ve Booker (1981)unclassified
See 3 more Smart Citations
“…Bu analitik yaklaşım ile yapılan parametrik çalışmalarda odometrik elastisite modülü değeri, iyileştirme faktörü ve oturma azaltma faktörü ile lineer olmayan bir değişim göstermektedir (Şekil 4). Odometrik elastisite modülü oranının oturma azalma faktörüne etkisi Castro ve Segaseta [6] yöntemine benzer sonuçlar vermektedir ancak değerler daha düşük elde edildiği için daha güvenli tarafta kalmaktadır. İki yöntem de kolon ve zeminin deformasyonu için elastisite teorisini esas almış olsa da, Balaam ve Booker [4]'in yanal deformasyonların yatay bileşenini hesaba katması daha muhafakazar sonuçlar vermektedir.…”
Section: Balaam Ve Booker (1981)unclassified
“… Castro ve Segaseta [6] yönteminde, odometrik elastisite modülü oranının (E mc /E ms ) fazla olması durumunda çok yüksek iyileştirme faktörü değerleri elde edilecektir. Bu değerler uygulamada elde edilenlerden oldukça fazladır.…”
Section: Sonuçlarunclassified
See 2 more Smart Citations
“…Han and Ye (2002) demonstrated that smear and well resistance reduced the rate of consolidation of stone column-reinforced foundations. Castro and Sagaseta (2011) presented an analytical solution to study the settlement reduction and the acceleration of consolidation by encased stone columns. Their results showed the encasement had a negligible effect on the consolidation for an elastic column but had a positive effect when the column started to yield.…”
Section: Introductionmentioning
confidence: 99%